Observations of O vi Absorption from the Superbubbles of the Large Magellanic Cloud. Issue Volume 9:Issue S296(2013) (29th January 2014) - Pradhan, Ananta C.; Pathak, Amit; Murthy, Jayant; Ojha, D. K.
Abstract: We have presented the observations of O VI absorption at 1032 Å towards 22 sightlines in 10 superbubbles (SBs) of the Large Magellanic Cloud (LMC) using the data obtained from the Far Ultraviolet Spectroscopic Explorer (FUSE) . The estimated abundance of O VI in the SBs varies from a minimum of (1.09 ±0.22)×10 14 atoms/cm 2 in SB N206 to a maximum of (3.71±0.23)×10 14 atoms/cm 2 in SB N70. We find about a 46% excess in the abundance of O VI in the SBs compared to the non-SB lines of sight. Even inside a SB, O VI column density (N(O VI)) varies by about a factor of 2 to 2.5. These data are useful in understanding the nature of the hot gas in SBs.